Nitrilotriacetic Acid Improves Plasma Electrolytic Oxidation of Titanium for Biomedical Applications - Kyrylenko, S.; Sowa, M.; Kazek-Kęsik, A.; Stolarczyk, A.; Pisarek, M.; Husak, Y.; Korniienko, V.; Deineka, V.; Moskalenko, R.; Matuła, I.; Michalska, J.; Jakóbik-Kolon, A.; et al. (My University, 2023)
Dental implants have become a routine, affordable, and highly reliable technology to replace tooth loss. In this regard, titanium and its alloys are the metals of choice for the manufacture of dental implants because they are chemically inert and biocompatible. However, for special cohorts of patients, there is still a need for improvements, specifically to increase the ability of implants to integrate into the bone and gum tissues and to prevent bacterial infections that can subsequently lead to periimplantitis and implant failures. Therefore, titanium implants require sophisticated approaches to improve their postoperative healing and longterm stability. Such treatments range from sandblasting to calcium phosphate coating, fluoride application, ultraviolet irradiation, and anodization to increase the bioactivity of the surface. Plasma electrolytic oxidation (PEO) has gained popularity as a method for modifying metal surfaces and delivering the desired mechanical and chemical properties. The outcome of PEO treatment depends on the electrochemical parameters and composition of the bath electrolyte. In this study, we investigated how complexing agents affect the PEO surfaces and found that nitrilotriacetic acid (NTA) can be used to develop efficient PEO protocols. The PEO surfaces generated with NTA in combination with sources of calcium and phosphorus were shown to increase the corrosion resistance of the titanium substrate. They also support cell proliferation and reduce bacterial colonization and, hence, lead to a reduction in failed implants and repeated surgeries. Moreover, NTA is an ecologically favorable chelating agent. These features are necessary for the biomedical industry to be able to contribute to the sustainability of the public healthcare system. Therefore, NTA is proposed to be used as a component of the PEO bath electrolyte to obtain bioactive surface layers with properties desired for next-generation dental implants.
Keywords: dental implant; surface processing; plasma electrolytic oxidation; complexing agent; corrosion resistance; biocompatibility